Variations of aldehyde emission from representative tree species in urban forests by climate change. (1st October 2021) - Jung, Yoo-Jin; Son, Youn-Suk; Park, Shin-Young; Choi, In-Young; Ahn, Ji-Won; Son, Joung-A; Oh, Chang Young; Dinh, Trieu-Vuong; Kim, Jo-Chun
Abstract: The aldehydes emitted from the main tree species composing the urban forest in South Korea were investigated. P. sargentii, Z. serrata, G. biloba, T. cuspidata, and M. glyptostroboides were considered target tree species. Variations of aldehyde emission rates were observed in relation to photosynthetic activity, temperature and photosynthetically active radiation (PAR) conditions. By comparing the apparent quantum yield (AQY) results indicating photosynthetic activity with the aldehyde ER results, it was confirmed that the photosynthetic characteristics of the trees influence the aldehyde emission. The highest standard emission rate (at a standard condition: 30 °C and 1000 μmol m −2 s −1 ) of total aldehyde was found in Z. serrata (i.e., 964.9 ng gdw −1 h −1 ). On the other hand, the tree with the lowest standard emission rate was G. biloba (i.e., 164.6 ng gdw −1 h −1 ). The composition ratios of emitted aldehydes differed according to the kind of tree. For most trees, formaldehyde and acetaldehyde emissions were of high proportions, and their standard emission rates showed the highest value among all aldehyde components. Two models (the T80 model considering only the temperature, and the G93 model considering the effect of both temperature and PAR) were used to calculate the standard aldehyde emission rate, and their correlation coefficient values compared by tree species. However, both models showed low correlation coefficients (below 0.77 (r 2 )) at all target trees. Graphical abstract: Image 1 Highlights: Aldehyde emission rates (ERs) of main tree species in urban forests were investigated. G93 and T80 models were applied to compare the standard ERs of aldehyde. G. biloba showed the lowest aldehyde ERs, Z. serrata revealed the highest one. Aldehyde ERs is closely related to the AQY of trees. Those two models were found unsuitable for evaluating the standard ERs of aldehyde.